(untitled) (Research, Society and Development, 2020)
Objective: to describe the management of the routine of day-to-day work for analysis of the quality of nursing teams, through an internal audit, to determine the non-conformities in the care of the severely ill patient with COVID-19. Method: this is an experience report of the application of the routine routine model of day-to-day work in the internal audit of the ICU of a university hospital in Rio de Janeiro. The study had four phases, data collection was performed through interview with form, by a nurse specialized in the japanese total quality management model. The Plan, Do, Check and Act (PCDA) cycle, descriptive analysis and Pareto analysis were used. Results: even after the supervision of the interprofessional nursing teams by the nursing care coordinators, 94% of the teams did not modify their behavior and were in non-conformities, evaluated by nursing evolutions, compliance with medical prescriptions, script of shift and notifications of adverse events sensitive to nursing care. Final considerations: although the quality control of nursing care by the nurse managers is effective, the internal audit showed that, directly or indirectly, the anomalies were related to: direct supervision of nursing with uninterrupted use of Personal Protective Equipment (PPE); use of ineffective communication strategies; lack of rigor in the process of evaluating the admission of new nursing professionals; standard operating procedures in non-conformity and poor training performed in the admission of interprofessional teams to act in the treatment of COVID-19 in the ICU.